2019
DOI: 10.3390/ijms20215335
|View full text |Cite
|
Sign up to set email alerts
|

The Yin-Yang Regulation of Reactive Oxygen Species and MicroRNAs in Cancer

Abstract: Reactive oxygen species (ROS) are highly reactive oxygen-containing chemical species formed as a by-product of normal aerobic respiration and also from a number of other cellular enzymatic reactions. ROS function as key mediators of cellular signaling pathways involved in proliferation, survival, apoptosis, and immune response. However, elevated and sustained ROS production promotes tumor initiation by inducing DNA damage or mutation and activates oncogenic signaling pathways to promote cancer progression. Rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 140 publications
(162 reference statements)
0
29
0
Order By: Relevance
“…Several studies showed that T 3 –THRs–TREs signaling affects miRNAs expression ( Dong et al, 2010 ; Janssen et al, 2014 ; Babu and Tay, 2019 ). For instance, T 3 –THRs–TREs binds to miR-17 promoter and decreases transcription and processing of mature miR-17, involved in cancer ( Lin Y. H. et al, 2013b ).…”
Section: Interplay Between Ths Wnt Pathway and Mirnas During Inflammentioning
confidence: 99%
“…Several studies showed that T 3 –THRs–TREs signaling affects miRNAs expression ( Dong et al, 2010 ; Janssen et al, 2014 ; Babu and Tay, 2019 ). For instance, T 3 –THRs–TREs binds to miR-17 promoter and decreases transcription and processing of mature miR-17, involved in cancer ( Lin Y. H. et al, 2013b ).…”
Section: Interplay Between Ths Wnt Pathway and Mirnas During Inflammentioning
confidence: 99%
“…Homogenous KRAS G12D mutant, a common mutation causing dysregulation of the MAPK pathway, has been reported to favor glucose fueled TCA cycling due to glucose metabolic reprogramming and reactive oxygen species (ROS) management, leading to increased malignancy [255]. The interplay between miRNA and ROS in cancer treatment response has been discussed in recent reviews [256,257]. Non-coding RNAs such as miR-21 and miR-30c have shown upregulation with KRAS G12D overexpression, which as a result enhance regulation of Ras downstream pathways [207].…”
Section: Ras/raf/mek/erk (Mapk)mentioning
confidence: 99%
“…Moreover, it is interesting to note that different subtypes of BC have different levels of ROS production among which TNBC shows the highest level of ROS [136]. A recent review by Babu and Tay on ROS signaling in cancer progression mentions an excisting crosstalk between ROS and miRNA regulation [137]. ROS can affect the miRNA expression by different mechanisms, such as epigenetic modulation of miRNA or by modifying the expression of transcription factors involved in the miRNA biogenesis.…”
Section: Ros Sensing Mirnas and Tumor Angiogenesismentioning
confidence: 99%